2015
DOI: 10.1021/acs.jpcc.5b05818
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Mapping of Layer-Dependent Surface Potential and Junction Properties of CVD-Grown MoS2 Domains

Abstract: In the present study, nanoscale variations in the work function values and the resulting changes in junction properties of chemical vapour deposited two-dimensional (2D) MoS 2 domains has been investigated as a function of number of layers using Kelvin Probe Force Microscopy (KPFM) and Conductive Atomic Force Microscopy(CAFM) techniques. Raman spectroscopy has been employed to obtain the magnitude of difference between E 2g and A 1g peaks which has been used as a signature of the number of layers. Surface pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 42 publications
8
35
1
Order By: Relevance
“…The inset line‐profile shows the contact potential difference (CPD) between tip and the sample or the substrate. The CPD for the ML MoS 2 and the substrate was found to be −200 V and −400 V respectively and hence, the work function to be 4.93 eV and 4.73 eV respectively which is in agreement with the reported work function of ML MoS 2 . Our observed value of work function (4.93 eV) suggests the non‐existence of MoO 3 phase in our sample .…”
Section: Resultssupporting
confidence: 89%
“…The inset line‐profile shows the contact potential difference (CPD) between tip and the sample or the substrate. The CPD for the ML MoS 2 and the substrate was found to be −200 V and −400 V respectively and hence, the work function to be 4.93 eV and 4.73 eV respectively which is in agreement with the reported work function of ML MoS 2 . Our observed value of work function (4.93 eV) suggests the non‐existence of MoO 3 phase in our sample .…”
Section: Resultssupporting
confidence: 89%
“…In the expression for the tunneling probability T, we use Φ s = 5.1 eV (work function of monolayer MoS 2 ) [53][54] or 5.8 eV (work function of monolayer WS 2 ) [55], and Φ t = 4.5 eV (work function of tungsten metal tip). We assume that tunneling is dominated by the behavior at the K/K' points the Brillouin zone and consequently use [56].…”
Section: B Determination Of Quasi-particle Band Gaps From Sts Datamentioning
confidence: 99%
“…We have observed that the contribution from the local electrostatic component to the lateral deflection is minimal (in the range of 0.05–0.1 pm/V) in the current measurements. The reasons for the minimal contribution are the large lateral spring constant of the AFM tip used (20–25 N/m) and the smaller surface potential difference for MoS 2 (0.1–0.4 V) 35 , 36 . By extracting various contributions from Eqs.…”
Section: Resultsmentioning
confidence: 99%